Critérios de utilização e escolha de dentifrício nas clínicas da Faculdade de Odontologia da Universidade de Passo Fundo - Aguiar, Luana Savi de (2019)
Fluoride plays an important role in the prevention and decline of caries disease, among which fluoride toothpaste is considered the simplest and most rational method of using fluoride, since it combines the mechanical removal of biofilm with the therapeutic effects of fluoride. However, the minimum requirement for a dentifrice to have anti-caries potential is to have a formulation with fluoride in the proper concentration. The objective of this study was to evaluate the criteria and the choice in the use of fluoridated toothpastes by children who sought dental care at the Faculty of Dentistry of the University of Passo Fundo in the northern region of the state of Rio Grande do Sul. Observational cross-sectional research, being carried out at the Dental Clinics of the Faculty of Dentistry of the University of Passo Fundo, through a questionnaire carried out directly to the minor and/or the person responsible for the child. 102 children, invited and available, participated in the study. The results showed that of the (84.31%) children interviewed attended the FO-UPF clinics, of these only (10.78%) reported that they introduced the dentifrice before 1 year and the choice of dentifrice is made by the brand having as preference Colgate (31.37%) and most respondents mentioned using their parents' toothpaste (71.57%). It is concluded that the criteria and the choice of toothpaste by the interviewees were in accordance with the concentration and quantity disposed on the toothbrush, thus existing a relationship between health and price.